Variation among macroinvertebrate communities suggests the importance of conserving desert springs. Issue 4 (16th April 2018) - Stanislawczyk, Keara; Walters, Ashley D.; Haan, Tara J.; Sei, Makiri; Lang, Brian K.; Berg, David J.
Abstract: Desert springs are highly threatened ecosystems inhabited by a substantial number of endemic species. Macroinvertebrate communities of five springs in the northern Chihuahuan Desert of west Texas and south‐eastern New Mexico were sampled seasonally. Rather than focusing on individual taxa, this study examined the community structure of springs to identify patterns that are likely to reflect both local conditions and potential dispersal barriers. In total, 46 774 individuals representing 109 taxa were collected with high relative abundances of gastropods, amphipods, and oligochaetes. Spatial variation in community composition was greater than temporal variation. Although there were differences in the salinity content and concentrations of several major anions and cations among sites, these were not significant predictors of difference in community structure. Two springs sharing the same groundwater source contained similar macroinvertebrate communities and had similar physicochemical conditions. Results from this study suggest that springs in the northern Chihuahuan Desert contain unique communities and endemic species owing to historical processes such as isolation and dispersal limitation, rather than contemporary processes such as environmental filtering and species sorting. Springs located in the northern Chihuahuan Desert, like those located in other arid regions of the world, are valuable for their biodiversity because of their distinct invertebrate communities and high rates of endemism. Thus, they should be conserved individually to ensure the preservation of unique species and communities.